Encapsulation bioactive compund propolis with carrageenan –gum arabic by spray drying - Denni Kartika Sari; Retno Sulistyo Dhamar Lestari; Prasetyo Khinanta; Muhammad Sahlan (JURNAL INTEGRASI PROSES, 2020)
Propolis is a product from the honeybee particularly from flowers , leaf buds, plant resins that bee collected as building material. Propolis exerts numerous pharmacological activities such as antioxidant, anti bacterial, anticancer, antifungal, anti inflammatory, antiviral etc. There are growing interest In the food industry in microencapsulation to protect, isolate or control the release of given substances. Spray drying is one of many methods to encapsulate food ingredients. Microcapsules were produced by a spray-drying technique using of solution of k–carrageenan gum arabic and maltodextrin as the binding materials. In this work, the effects of spray-drying on the encapsulation yield, particle size and total phenolic content of the bioactive components of propolis were determined for different concentration between carrier agent and propolis at volume ratio 1:0,5 1:1, 1:1,5,1. The SEM testing showed that the microcapsules had a regular spherical shape with the size 1 µm. The spray-dried propolis extract showed high total phenolic content 67,78 mg(GAE)/g extract at ratio 1:2, and the highest yield at concentration ratio between carrier agent and propolis 1:0,5 are 64,7 %.